Analisis Determinan Makroekonomi Inflasi dan Konsumsi Rumah Tangga terhadap Penerimaan Pajak Pertambahan Nilai (PPN) dan Pajak Penjualan atas Barang Mewah (PPnBM) di Indonesia - Ilham Febri Budiman (Universitas 45 Surabaya, 2025)
This article identifies and examines the determinants of state revenue in the taxation sector specifically on VAT and STLG in Indonesia. The main objective of this study is to analyze whether inflation and household consumption affect VAT and STLG revenues along with how much influence these determinants have. The type of research used is quantitative with descriptive statistical analysis methods. Techniques to analyze the effect of inflation and household consumption on VAT and STLG revenue variables used descriptive analysis, classical assumption tests and also multiple linear regression tests using statistical application platforms. The results of the research analysis identified that simultaneously, inflation and household consumption affect VAT and STLG revenues. So that if inflation and household consumption increase, then VAT and STLG revenues also increase, as well as in the opposite condition. The findings are in line with previous research, theories and hypotheses formulated.